Bi-component high-strength repair mortar material and preparation method thereof
By using modified cement and silica fume crosslinking reaction in a two-component high-strength repair mortar material, a three-dimensional network structure is formed, which solves the problems of slow improvement in compressive and flexural strength and high shrinkage rate in existing technologies. This achieves efficient interfacial bonding and early strength improvement, thereby enhancing the overall performance of the repair material.
Patent Information
- Application Number
- CN202510907850.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-10-31
AI Technical Summary
Existing repair mortar materials have problems in concrete structure maintenance and repair, such as slow improvement of compressive and flexural strength, high shrinkage rate, and weak bonding with old concrete interface, which affect the repair effect and the integrity and durability of the structure.
A two-component high-strength repair mortar material is adopted, including component A, which consists of modified cement, sulfoaluminate early-strength cement and water-based resin, and component B, which consists of silica fume, silane, cellulose ether, etc. A three-dimensional network structure is formed through the cross-linking reaction of modified silica fume and water-based resin. The setting time is controlled by adjusting the ratio of modified cement to sulfoaluminate cement, thereby improving early strength and interfacial adhesion.
It significantly improves the compressive and flexural strength of the repair mortar, reduces the shrinkage rate, enhances the interfacial bond with old concrete, improves repair efficiency and quality, and meets construction requirements.
Smart Images

Figure BDA0005479124700000041 
Figure BDA0005479124700000051
Abstract
Description
Technical Field
[0001] This invention pertains to the preparation technology of cement-based repair materials, specifically relating to a two-component high-strength repair material and its preparation method. Background Technology
[0002] Repair mortar is a specialized cement-based polymer mortar used for repairing and reinforcing surface defects in concrete structures. It possesses high compressive strength, adhesion, crack resistance, and waterproofing. This repair mortar is a polymer-modified cement-based dry-mix mortar, primarily used for repairing concrete defects, reinforcing and renovating old buildings and bridges. It is the preferred material when the thickness of the concrete surface damage is less than 50 mm. It exhibits good compatibility and excellent adhesion, meeting the requirements for compressive strength, flexural strength, abrasion resistance, flexibility, and low shrinkage in repair projects. It is characterized by convenient construction, good workability, good hanging performance, and ease of application to the facades and tops of components. Furthermore, the hardened material has a good appearance and excellent durability. This product can be used to repair cracked concrete surfaces in industrial and civil buildings, or to repair damaged industrial and civil buildings that do not meet design requirements.
[0003] However, in the maintenance and repair of concrete structures, repair mortar produced by traditional technology often has problems such as slow increase in compressive and flexural strength after 24 hours, high shrinkage rate, and weak bonding force with the old concrete interface, resulting in poor repair effect and affecting the integrity and durability of the structure.
[0004] Therefore, developing a repair mortar that can harden quickly, effectively reduce shrinkage, and improve interfacial adhesion is of great significance for improving repair efficiency and quality. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a two-component high-strength repair material and its preparation method.
[0006] To solve the above-mentioned technical problems, the solution adopted by the present invention is:
[0007] A two-component high-strength repair mortar material is provided, which is composed of the following raw material components in parts by weight:
[0008] Component A consists of 10-30 parts modified cement, 340-450 parts sulfoaluminate early-strength cement, and 10-30 parts water-based resin.
[0009] Component B consists of 3-15 parts silica fume, 3-12 parts silane, 0.3-0.6 parts cellulose ether, 0.5-2.5 parts redispersible latex powder, 0-3 parts short fibers, 0.3-1.5 parts polycarboxylate superplasticizer, and 0.3-0.9 parts defoamer.
[0010] As a preferred embodiment of the present invention, it further includes river sand with a particle size of 80 to 120 mesh, and the mass ratio of the sand to component A is 1:1.
[0011] As a preferred embodiment of the present invention, the modified cement is a compound of ordinary silicate cement and gypsum, with a mass ratio of 5-28:2-6.
[0012] As a preferred embodiment of the present invention, the waterborne resin is at least one of waterborne epoxy resin, waterborne acrylic resin, and waterborne polyurethane resin.
[0013] As a preferred embodiment of the present invention, the silane is one or more of KH450, KH550, KH570 or PEG-modified silane.
[0014] As a preferred embodiment of the present invention, the cellulose ether is hydroxypropyl methylcellulose, low-viscosity cellulose, microcrystalline cellulose or carboxymethyl cellulose; the redispersible latex powder is vinyl acetate-ethylene copolymer, vinyl acetate-ethylene tert-carbonate copolymer or polyvinyl butyral.
[0015] As a preferred embodiment of the present invention, the short fiber is PP fiber, polyester fiber or nylon fiber; the polycarboxylate superplasticizer is Sika 530P, Sika 540P or BASF F10.
[0016] As a preferred embodiment of the present invention, the defoamer is a polyether defoamer 362, Zhubao PD-2000A, or Mok DF830.
[0017] This invention further provides a method for preparing the aforementioned two-component high-strength repair mortar material, comprising the following steps:
[0018] (1) Weigh each raw material component according to the mass ratio stated above;
[0019] (2) Mix the modified cement, sulfoaluminate cement and water-based resin evenly at room temperature. The resulting mixture is component A. Seal and store for later use.
[0020] (3) Dissolve silane in an appropriate amount of ethanol, then add silica fume; stir at 200-500 rpm for 15-20 min at 80°C to obtain a uniform and stable liquid, and then dry the liquid at 80°C to obtain powder.
[0021] (4) Add polycarboxylate superplasticizer, defoamer, redispersible latex powder, cellulose ether and short fiber to the powder in step (3) in sequence, stir evenly to obtain the powder component B, and seal for later use.
[0022] The present invention also provides a method for using the two-component high-strength repair mortar material prepared by the aforementioned method, comprising the following steps:
[0023] (1) According to the requirements of the construction plan, the base surface of the concrete structure to be repaired shall be treated;
[0024] (2) Take component A and component B at a mass ratio of 1:3% to 5% and mix them evenly at room temperature; then add river sand of the same mass as component A and an appropriate amount of water, and stir evenly to obtain mixed mortar.
[0025] (3) Spread the mixed mortar on the base surface of the concrete structure to be repaired, smooth the surface and dry it at room temperature for 8 hours.
[0026] Compared with the prior art, the technical advantages of the present invention are:
[0027] 1. Existing repair mortar materials often use silica fume, which can significantly improve the compressive and flexural strength of concrete, especially in harsh environments such as chloride pollution, sulfate attack, and high humidity, significantly reducing the permeability and corrosivity of concrete and improving its durability. It also improves the wear resistance of concrete and extends its service life. However, the silica fume reaction consumes a large amount of water, which can lead to increased shrinkage and even cracking of the repair mortar after construction. This invention innovatively proposes to modify silica fume using silanes. During the modification process, silanol groups dehydrate and condense with the silanol groups on the silica fume surface, forming stable Si-O-Si covalent bonds. This reduces the water adsorption of the modified silica fume, avoiding the risk of cracking in the repair mortar.
[0028] 2. In this invention, component B can serve as an auxiliary component for the curing of the water-based resin in component A. Through the reaction of components A and B, and simultaneously with cement hydration, a cross-linking reaction occurs in the system, forming a three-dimensional network structure that is cross-linked with the cement hydration products, thereby giving the mortar certain mechanical properties. Furthermore, mortars with added water-based resin often suffer from problems such as excessively long drying times and insufficient early strength. This invention allows for adjustment of the relative addition amount of component B according to construction requirements, thereby controlling the setting time of the repair mortar, improving the early strength of the mortar with added water-based resin, and simultaneously enhancing the weather resistance of the water-based resin.
[0029] 3. The system of this invention uses the blending and water-reaction of components A and B. The purpose is to generate a certain amount of heat when the modified cement undergoes a hydration reaction, which causes the resin to react with the modified silica fume. The silica fume is embedded in the resin network, blocking the defect pores in the epoxy resin, reducing the porosity, and improving the overall strength of the mortar.
[0030] 4. This invention can adjust the setting time by adjusting the ratio between modified cement and sulfoaluminate cement according to the needs of the project construction plan, thus providing convenience for construction.
[0031] 5. The water-based resin and other raw materials used in this invention have low VOC content (almost 0), which reduces the production cost of repair mortar.
[0032] 6. This invention changes the pH value of the repair mortar material by adjusting the addition ratio of the water-reducing agent, which enables components A and B to react fully and avoids uneven mixing. Detailed Implementation
[0033] Part One: Implementation Scheme of the Invention
[0034] 1. Formula for two-component high-strength repair mortar:
[0035] Repair mortar material is composed of the following raw material components in parts by weight:
[0036] Component A consists of 10-30 parts modified cement, 340-450 parts sulfoaluminate early-strength cement, and 10-30 parts waterborne resin; wherein the modified cement is a compound of ordinary silicate cement and gypsum, with a mass ratio of 5-28:2-6; the waterborne resin may be at least one of waterborne epoxy resin, waterborne acrylic resin, and waterborne polyurethane resin.
[0037] Component B consists of 3–15 parts silica fume, 3–12 parts silane, 0.3–0.6 parts cellulose ether, 0.5–2.5 parts redispersible latex powder, 0–3 parts short fibers, 0.3–1.5 parts polycarboxylate superplasticizer, and 0.3–0.9 parts defoamer. The silane is one or more of KH450, KH550, KH570, or PEG-modified silane; the cellulose ether is hydroxypropyl methylcellulose, low-viscosity cellulose (viscosity less than 100 mPa·s), microcrystalline cellulose, or carboxymethyl cellulose; the redispersible latex powder is vinyl acetate-ethylene copolymer, vinyl acetate-ethylene tert-carbonate copolymer, or polyvinyl butyral; the short fibers are PP fibers, polyester fibers, or nylon fibers; and the polycarboxylate superplasticizer is Sika 530P, Sika 540P, or BASF F10. The defoamer is a polyether defoamer 362, Zhubao PD-2000A, or Mok DF830. River sand, with a mass ratio of 1:1 to component A, has a particle size of 80-120 mesh.
[0038] 2. Preparation method of two-component high-strength repair mortar material:
[0039] (1) Weigh each raw material component according to the mass ratio stated above;
[0040] (2) Mix the modified cement, sulfoaluminate cement and water-based resin evenly at room temperature. The resulting mixture is component A. Seal and store for later use.
[0041] (3) Dissolve silane in an appropriate amount of ethanol, then add silica fume; stir at 200-500 rpm for 15-20 min at 80°C to obtain a uniform and stable liquid, and then dry the liquid at 80°C to obtain powder.
[0042] (4) Add polycarboxylate superplasticizer, defoamer, redispersible latex powder, cellulose ether and short fiber to the powder in step (3) in sequence, stir evenly to obtain the powder of component B, and seal for later use.
[0043] 3. Application method of two-component high-strength repair mortar:
[0044] (1) According to the requirements of the construction plan, the base surface of the concrete structure to be repaired shall be treated;
[0045] (2) Take component A and component B at a mass ratio of 1:3% to 5% and mix them evenly at room temperature; then add river sand of the same mass as component A and an appropriate amount of water, and stir evenly to obtain mixed mortar.
[0046] (3) Spread the mixed mortar on the base surface of the concrete structure to be repaired, smooth the surface and dry it at room temperature for 8 hours.
[0047] Part Two: Examples and Comparative Cases
[0048] Referring to the contents described in Part 1 and according to the parameters listed in Table 1, the mixed mortars of Examples 1-5 were prepared respectively.
[0049] Table 1
[0050]
[0051]
[0052] Comparative Example 1
[0053] Referring to patent publication CN116621545A, a high corrosion-resistant marine repair mortar is prepared by weight fraction of the following components: 35-42 parts of high belite sulfoaluminate cement, 0.5-2 parts of binder, 50-60 parts of aggregate, 4-6.5 parts of asphalt-modified rubber powder, 0-0.5 parts of anhydrous gypsum, 0.15-0.2 parts of water-reducing agent, 0.16-0.2 parts of retarder, and 0.05-0.1 parts of early-strength agent.
[0054] Comparative Example 2
[0055] Referring to patent publication CN118619624A, a penetrating crystalline repair mortar suitable for humid environments is prepared according to the following components and steps: including cement, dried sand, silica fume, sodium silicate, basalt fiber, alkali activator, polybutylene terephthalate, brucite, hydroxyplatinic acid, and cellulose ether; in preparation, cement, silica fume, basalt fiber, cellulose ether, PBT, and hydroxyplatinic acid are first added to a container and stirred and mixed evenly to obtain a fiber mixed powder; dried sand and brucite are then added to the mixed powder and stirred and mixed evenly to obtain a mixture; then potassium hydroxide is completely dissolved in water to prepare an alkaline activating solution, and the alkaline activating solution and sodium silicate are added to the above mixture and stirred and reacted to obtain the repair mortar.
[0056] Part Three: Product Performance Testing and Results Analysis
[0057] 1. Testing Method
[0058] (1) In accordance with the provisions of JC / T985-2021, concrete samples were poured using the mortar prepared in Examples 1-5 and Comparative Examples 1-2, and then tested.
[0059] 2. Test Results and Analysis
[0060] Based on the same testing method, the performance test parameters of the products in Examples 1-5 and Comparative Examples 1-2 are shown in Table 2.
[0061] Table 2
[0062] sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 28-day compressive strength / MPa 54.2 56.8 51.5 50.6 55.4 52.8 45 28-day flexural strength / MPa 10.5 11.2 11.6 10.8 9.8 10.5 7 Size shrinkage % 0.021 0.04 0.035 0.05 0.053 0.07
[0063] As can be seen from the data in Table 1, Examples 1-5 of the present invention exhibit optimal performance, mainly reflected in higher compressive and flexural strength, and superior dimensional shrinkage. Furthermore, all examples show better performance compared to the comparative examples.
[0064] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A two-component high-strength repair mortar material, characterized in that, This repair mortar material is composed of the following raw material components in parts by weight: Component A consists of 10-30 parts modified cement, 340-450 parts sulfoaluminate early-strength cement, and 10-30 parts water-based resin. Component B consists of 3-15 parts silica fume, 3-12 parts silane, 0.3-0.6 parts cellulose ether, 0.5-2.5 parts redispersible latex powder, 0-3 parts short fibers, 0.3-1.5 parts polycarboxylate superplasticizer, and 0.3-0.9 parts defoamer.
2. The two-component high-strength repair mortar material according to claim 1, characterized in that, It also includes river sand with a particle size of 80-120 mesh, with a mass ratio of 1:1 to component A.
3. The two-component high-strength repair mortar material according to claim 1, characterized in that, The modified cement is a blend of ordinary silicate cement and gypsum, with a mass ratio of 5-28:2-6.
4. The two-component high-strength repair mortar material according to claim 1, characterized in that, The waterborne resin is at least one of waterborne epoxy resin, waterborne acrylic resin, and waterborne polyurethane resin.
5. The two-component high-strength repair mortar material according to claim 1, characterized in that, The silane is one or more of KH450, KH550, KH570 or PEG-modified silane.
6. The two-component high-strength repair mortar material according to claim 1, characterized in that, The cellulose ether is hydroxypropyl methylcellulose, low-viscosity cellulose, microcrystalline cellulose, or carboxymethyl cellulose; the redispersible latex powder is vinyl acetate-ethylene copolymer, vinyl acetate-ethylene tert-carbonate copolymer, or polyvinyl butyral.
7. The two-component high-strength repair mortar material according to claim 1, characterized in that, The short fibers are PP fibers, polyester fibers, or nylon fibers; the polycarboxylate superplasticizer is Sika 530P, Sika 540P, or BASF F10.
8. The two-component high-strength repair mortar material according to claim 1, characterized in that, The defoamer is a polyether defoamer 362, Zhubao PD-2000A, or Mok DF830.
9. The method for preparing the two-component high-strength repair mortar material according to any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Weigh each raw material component according to the mass ratio stated above; (2) Mix the modified cement, sulfoaluminate cement and water-based resin evenly at room temperature. The resulting mixture is component A. Seal and store for later use. (3) Dissolve silane in an appropriate amount of ethanol, then add silica fume; stir at 200-500 rpm for 15-20 minutes at 80°C, and then dry the liquid at 80°C to obtain powder. (4) Add polycarboxylate superplasticizer, defoamer, redispersible latex powder, cellulose ether and short fiber to the powder in step (3) in sequence, stir evenly to obtain the powder of component B, and seal for later use.
10. The method of using the two-component high-strength repair mortar material prepared by the method of claim 9, characterized in that, Includes the following steps: (1) According to the construction plan requirements, the base surface of the concrete structure to be repaired shall be treated; (2) Take component A and component B at a mass ratio of 1:3% to 5% and mix them evenly at room temperature; then add river sand of the same mass as component A and an appropriate amount of water, and stir evenly to obtain mixed mortar. (3) Spread the mixed mortar on the base surface of the concrete structure to be repaired, smooth the surface and dry it at room temperature for 8 hours.
Citation Information
Patent Citations
High-corrosion-resistance maritime work repair mortar and preparation method thereof
CN116621545A
Capillary crystalline repair mortar suitable for humid environment and preparation method thereof
CN118619624A
Cited By
Interface enhanced self-healing low shrinkage concrete repair mortar and preparation method thereof
CN122464669A